PENDAMPINGAN PENGEMBANGAN DESA WISATA TAMANMARTANI - Putra, Tegar Satya; Yennie, Yennie; Murti, Desideria Cempaka Wijaya; Fauzi, Gilang Ahmad; Prihatno, Prihatno (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
Abstract: The development of tourism villages has become one of the government's strategies to improve the welfare of local communities and encourage economic growth. Tamanmartani Tourism Village, one of the tourism villages in Indonesia, has great potential to develop. However, the village also faces several challenges, such as a low level of cooperation, ineffective communication, lack of clean production application, and lack of understanding of social media and digital marketing. To overcome these challenges, three types of training were organized for stakeholders in Tamanmartani Tourism Village. This training is divided into three groups, namely service improvement, digital marketing, and management. The results of the training show that the participants have a high level of engagement and a good understanding of the material taught. This training also provides tangible benefits for Tamanmartani Tourism Village. To improve all aspects that have been learned, consistent actions and involvement of all relevant stakeholders are required. Abstrak: Pengembangan desa wisata telah menjadi salah satu strategi pemerintah untuk meningkatkan kesejahteraan masyarakat lokal dan mendorong pertumbuhan ekonomi. Desa Wisata Tamanmartani, salah satu desa wisata di Indonesia, memiliki potensi besar untuk berkembang. Namun, desa tersebut juga menghadapi beberapa tantangan, seperti rendahnya tingkat kerjasama, komunikasi yang tidak efektif, kurangnya penerapan produksi bersih, dan kurangnya pemahaman tentang media sosial dan pemasaran digital. Guna mengatasi tantangan tersebut, tigas jenis pelatihan diselenggarakan bagi para pemangku kepentingan di Desa Wisata Tamanmartani. Pelatihan ini dibagi menjadi tiga kelompok, yaitu peningkatan pelayanan, pemasaran digital, dan manajemen. Hasil pelatihan menunjukkan bahwa peserta memiliki tingkat keterlibatan yang tinggi dan pemahaman yang baik terhadap materi yang diajarkan. Pelatihan ini juga memberikan manfaat nyata bagi Desa Wisata Tamanmartani. Untuk dapat meningkatkan seluruh aspek yang telah dipelajari, dibutuhkan tindakan yang konsisten dan keterlibatan seluruh pemangku kepentingan yang bersangkutan.